Determinants of Dividend Policy: An Empirical Research on Chinese market - zheng, juan (2009)
This paper intends to provide an analysis of dividend policy in China. It employs 354 listed companies over the period from 2001 to 2006 and identifies their determinants of dividend policy in Chinese Market. Both of generally used factors of dividend policy and Chinese specific elements are included in this paper. The annual reports from the official website of the exchange are the major source of financial data for the empirical research in this paper. In comparison with former researches, dividend payment in Chinese listed companies increase when earning per share, growth rate, firm size increase, which are positive correlated to firm’s dividend policy. However, debt ratio is found to be negatively related with dividend policy of the corporate in China. The correlation between return on equity and dividend level is not positive as former studies implied. The concentration of shares is not negative correlated to dividend payment as expected, which is opposite to tax clientele theory. The proportion of untradeable shares is positively related to the probability of dividend payment and negative related to stock dividend.